Mentor Tutoring: An Efficient Method for Teaching Laparoscopic Colorectal Surgical Skills in a General Hospital. Issue 6 (December 2017) - Ichikawa, Nobuki; Homma, Shigenori; Yoshida, Tadashi; Ohno, Yosuke; Kawamura, Hideki; Wakizaka, Kazuki; Nakanishi, Kazuaki; Kazui, Keizo; Iijima, Hiroaki; Shomura, Hiroki; Funakoshi, Tohru; Nakano, Shiro; et al.
Abstract : Objective: We retrospectively assessed the efficacy of our mentor tutoring system for teaching laparoscopic colorectal surgical skills in a general hospital. Materials and Methods: A series of 55 laparoscopic colectomies performed by 1 trainee were evaluated. Next, the learning curves for high anterior resection performed by the trainee (n=20) were compared with those of a self-trained surgeon (n=19). Results: Cumulative sum analysis and multivariate regression analyses showed that 38 completed cases were needed to reduce the operative time. In high anterior resection, the mean operative times were significantly shorter after the seventh average for the tutored surgeon compared with that for the self-trained surgeon. In cumulative sum charting, the curve reached a plateau by the seventh case for the tutored surgeon, but continued to increase for the self-trained surgeon. Conclusions: Mentor tutoring effectively teaches laparoscopic colorectal surgical skills in a general hospital setting.